Absolute magnetization of the seafloor at a basalt‐hosted hydrothermal site: Insights from a deep‐sea submersible survey. Issue 4 (18th February 2015) - Szitkar, Florent; Dyment, Jérôme; Fouquet, Yves; Choi, Yujin; Honsho, Chie
Abstract The analysis of high‐resolution vector magnetic data acquired by deep‐sea submersibles (DSSs) requires the development of specific approaches adapted to their uneven tracks. We present a method that takes advantage of (1) the varying altitude of the DSS above the seafloor and (2) high‐resolution multibeam bathymetric data acquired separately, at higher altitude, by an Autonomous Underwater Vehicle, to estimate the absolute magnetization intensity and the magnetic polarity of the shallow subseafloor along the DSS path. We apply this method to data collected by DSS Nautile on a small active basalt‐hosted hydrothermal site. The site is associated with a lack of magnetization, in agreement with previous findings at the same kind of sites: the contrast between nonmagnetic sulfide deposits/stockwork zone and strongly magnetized basalt is sufficient to explain the magnetic signal observed at such a low altitude. Both normal and reversed polarities are observed in the lava flows surrounding the site, suggesting complex history of accumulating volcanic flows.